Application of Payment Transactions At Polyclinic Bintaro By Using Microsoft Visual Basic 6.0 - Sondang Tiurma Julianti Sianturi (Jurnal Sistem Informasi, 2010)
By still many companies - companies that use an application using Dos under aless good result in the display - the display program and too complicated for theuser program to mengentry data in the transaction. Moving on from that, thewriter tries to make a payment transaction application programs that areexpected to simplify and accelerate the total processing of payment transactionsand enables the user application programs to provide information on the resultsof payment transactions to his superiors. Program applications created usingMicrosoft Visual Basic 6.0, the conclusion obtained is that by using thisapplication program to accelerate the total processing of payment transactionsand facilitate the user's application programs to provide information on theresults of payment transactions to his superiors, as well as in terms ofappearance of the application program looks a bit more interesting.